CRIMINOLOGICAL ANALYSIS OF THE PHENOMENON OF JUVENILE DELINQUENCY IN THE PANGKAJENE AND ISLANDS REGENCY AREA: CAUSING FACTORS, IMPACT AND COMMUNITY BASED PREVENTION EFFORTS - Astri Aryanti Amsyahar; M. Amsyahar (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study aims to analyze in depth the factors that cause juvenile delinquency, identify its impacts, and formulate effective and sustainable prevention efforts by involving the active role of the community. This study uses an empirical legal research method with a criminological approach. Data collection was conducted through direct observation, interviews with sources consisting of teenagers, parents, community leaders, law enforcement officers, and school officials, as well as the study of related documents. The data obtained were analyzed descriptively qualitatively to describe and explain the problems studied. The results of the study indicate that juvenile delinquency in Pangkep Regency is caused by the interaction of various factors, both from within the teenager and from their surrounding environment. Internal factors include psychological conditions, lack of legal understanding, and the search for identity, while external factors include family conditions, social environment, the influence of technology and information, and the socio-economic conditions of the community. Juvenile delinquency that occurs varies in form, ranging from acts that violate social norms to acts that are categorized as criminal acts, with impacts felt by individuals, families, and society at large. Handling juvenile delinquency cannot be done only with a law enforcement approach, but requires a comprehensive approach and involves all elements of society. Community-based prevention efforts are an effective strategy because they can reach the root of the problem and are implemented sustainably. This research recommends strengthening the role of community institutions, enhancing collaboration between various parties, and developing programs that support the development and potential of adolescents, so they can grow and develop into good and responsible citizens.